Sidero-Siliko Tuberkulosis pada Penderita Efusi Pleura Masif Dekstra yang Awalnya Dicurigai Keganasan: [Malignant Suspicion of Massive Pleural Effusion in Sidero-Silico Tuberculosis Patient] - Winariani Koesoemoprodjo; Hapsari Paramita Narendrani (Faculty of Medicine Universitas Airlangga, 2017)
Background: Pneumoconiosis defined as the accumulation of dust in the lungs and causes tissue reactions to mineral materials from various industries that affect the respiratory system. Among the causes of pneumoconiosis are silica dust (silicosis) and iron dust (ciderosis). Pneumoconiosis provides a pathological reaction in lung tissue due to inhaled deposition of mineral particulate dust or persistent fiber material. The risk of infection with tuberculosis is higher in patients with pneumoconiosis, especially silicosis. Most cases of pleural effusion are found in malignancies or infections such as tuberculosis but can also be a complication of pneumoconiosis. Case: A man, 55 years old, reported with a 2-week congested complaint that was getting worse, with a cough for almost 1 month. Patients with work history as iron lathers for 25 years with comorbid diabetes mellitus. From the results of our chest x-rays we get a picture of massive pleural effusion with a total evacuation of approximately 9 liters, whereas on the chest CT scan get a solid mass picture in the right lung field with multiple nodules in the liver. The results of bronkoalveolar rinses obtained silica and iron content, and obtained Mycobacterium tuberculosis culture in pleural fluid culture. Conclusion: Illustration of a case report of a 55-year-old man diagnosed as a sidero-silico-tuberculosis with a periodic picture of tuberculosis and pleural effusion in the right lung undergoing resolution with OAT treatment.